a) [TEX]S=\frac{1}{10.9}-\frac{1}{9.8}-\frac{1}{8.7}-...-\frac{1}{2.1} \\ =\frac{1}{10.9}-(\frac{1}{9.8}+\frac{1}{8.7}+...+\frac{1}{2-1}) \\ = \frac{1}{90}-(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}...+\frac{1}{8}-\frac{1}{9}) \\ = \frac{1}{90}-(1-\frac{1}{9}) = \frac{1}{90}-\frac{8}{9} = \frac{-79}{90} [/TEX]
b) [TEX]A=\frac{3}{1^2.2^2}+\frac{5}{2^2.3^2}+\frac{7}{3^2.4^2}+...+\frac{19}{9^2.10^2} \\ =\frac{3}{1.4}+\frac{5}{4.9}+\frac{7}{9.16}+...+\frac{19}{81.100} \\ \frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{9}+...+\frac{1}{81}-\frac{1}{100} \\ =\frac{1}{2}-\frac{1}{100}=\frac{49}{50}[/TEX]